Influence of the treatment medium temperature on lutein extraction assisted by pulsed electric fields from Chlorella vulgaris. (May 2015) - Luengo, Elisa; Martínez, Juan Manuel; Bordetas, Andrea; Álvarez, Ignacio; Raso, Javier
Abstract: Influence of the of temperature of biomass (10–40 °C) treated by pulsed electric fields (PEFs) at different intensities (10–25 kV/cm) on electroporation of the microalgae Chlorella vulgaris and on the extraction of lutein was investigated. The occurrence of reversible and irreversible electroporation increased with electric field strength and medium treatment temperature. On the other hand, increasing temperature increased the sensitivity of C. vulgaris cells to irreversible electroporation. Response surface methodology was used to identify optimal PEF treatment conditions for enhancing lutein extraction yield (LEY) from fresh C. vulgaris biomass. Considering the cultivation temperature of C. vulgaris (25–30 °C) and the low increase in the LEY when the PEF treatments were applied at temperatures above 30 °C, a treatment of 25 kV/cm–100 μs at 25–30 °C increased the LEY around 3.5–4.2-fold in comparison with the control, resulting in the most suitable treatment conditions for maximizing the lutein extraction at the lowest energy cost. Industrial relevance: In recent years, industrial interest in microalgae as source of bioproducts such as natural additives or active ingredients for food and cosmetic formulations has arisen. However, there are still several obstacles to fully take advantage, such as the ability to successfully extract these compounds from the cell biomass. Electroporation of microalgae by PEF-technology could be an alternative to conventional cell disruption techniques. Therefore, identifying critical factors affecting the enhancement of bioproduct extraction from microalgae is necessary to establish PEF as a true option. Highlights: Increasing medium temperature increased sensitivity towards electroporation. PEF improved lutein extraction yield up to 4.2-fold compared to the control. 25–30 °C resulted in the most suitable treatment temperature for subsequent extraction. PEF-treatments did not cause degradation of lutein extracts.